IPTEKS LELANG BARANG JAMINAN PADA PT. PEGADAIAN (PERSERO) CABANG KAROMBASAN MANADO - Taufik, Meisa Farina; Kalalo, Meily Y.B. (Universitas Sam Ratulangi, 2018)
PT. Pegadaian is an institution that runs a mortgage business, where an item or securities can be used as collateral to borrow some money. And if the pledge giver does not fulfill the obligations of an agreed time, PT. Pegadaian (Persero) will give a warning to repay the loan immediately. If the warning does not get clarity or confirmation of repayment from the mortgage provider, PT. Pegadaian (Persero) has the right to take repayment of its receivable by auctioning off collateral for money pawn under it’s control. This study ains to determine the implementation of the auction at PT. Pegadaian (Persero) Karombasan branch in Manado. Also to find out the obtacles to the auction at PT. Pegadaian (Persero) The data analysis technique uses descriptive analysis.Keywords: auction, constraints, implementation, mortgage goods